Eficacia y seguridad de la sedación consciente con midazolam en el abordaje odontológico de pacientes pediátricos con autismo. - Chávez Armas, Ana Christina (2025)
The main objective of this literature review was to examine the effectiveness and safety of midazolam for conscious sedation in dental consultations for children with autism spectrum disorder, through a systematized review of the available scientific literature identified, selected, and evaluated using the PRISMA methodology, globally recognized for its accuracy in synthesizing relevant studies. The most significant findings showed that midazolam, at doses of 0.5 mg/kg orally and 0.3 mg/kg sublingually, is capable of achieving an adequate balance between safety and efficacy. Furthermore, it was observed that autistic patients sedated with midazolam exhibit greater cooperation, reduced anxiety, and, most importantly, allow the performance of simple dental procedures, such as fillings and tartrectomies. As for adverse effects, these are usually mild and mainly related to high doses, leading to the conclusion that its safety profile is favorable, provided that proper clinical monitoring is ensured. In conclusion, midazolam stands out as an effective and safe tool for conscious sedation in pediatric dentistry, improving the patient experience and minimizing the need for more invasive interventions.